Influence of anxiety and depression on coping strategies to stress in adolescents from North Lima - Jiménez Noriega, Ricardo Enrique (2023)
The objective of this study was to determine the influence of depression and anxiety on coping strategies in adolescents in northern Lima. It had a sample of 273 adolescent students from an educational institution. The research was of a basic cross-sectional type. As for the statistical analysis, binary regression analysis was used. The results showed that depression and anxiety do not influence all coping styles, but specifically the coping styles of avoidance, emotional discharge and inactivity.